Sylvatic Dengue Virus Type 2 Activity in Humans, Nigeria, 1966 - Vasilakis, Nikos (Centers for Disease Control and Prevention, 2008)
Using phylogenetic analysis of complete virus genomes from human isolates obtained in Nigeria in 1966, we identified sylvatic dengue virus (DENV) strains from 3 febrile patients. This finding extends current understanding of the role of sylvatic DENV in febrile disease and documents another focus of sylvatic DENV transmission in West Africa.